Visible light sensitizer-catalyzed highly selective photo oxidation from thioethers into sulfoxides under aerobic condition - Cong Ye (Nature Portfolio, 2018)
Abstract We report herein a visible light sensitizer-catalyzed aerobic oxidation of thioethers, affording sulfoxides in good to excellent yields. The loading of the catalyst was as low as 0.1 mol%. The selectivity was excellent. Mechanism studies showed both singlet oxygen and superoxide radical anion were likely involved in this transformation.